2006
DOI: 10.1128/jb.00335-06
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing as an Approach for Population Analysis of Medicago -Nodulating Rhizobia

Abstract: Multilocus sequence typing (MLST), a sequence-based method to characterize bacterial genomes, was used to examine the genetic structure in a large collection of Medicago-nodulating rhizobial strains. This is the first study where MLST has been applied in conjunction with eBURST analysis to determine the population genetic structure of nonpathogenic bacteria recovered from the soil environment. Sequence variation was determined in 10 chromosomal loci of 231 strains that predominantly originated from southwest A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 29 publications
3
45
2
6
Order By: Relevance
“…In the case of M. polymorpha, out of four isolates, two were categorized as A. tumefaciens and one each as E. meliloti and E. medicae, respectively. Van Berkum et al (38) reported that the predominant symbiont of M. polymorpha is E. medicae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of M. polymorpha, out of four isolates, two were categorized as A. tumefaciens and one each as E. meliloti and E. medicae, respectively. Van Berkum et al (38) reported that the predominant symbiont of M. polymorpha is E. medicae.…”
Section: Discussionmentioning
confidence: 99%
“…Payakapong et al (25) isolated a highly salt tolerant Ensifer species (Ensifer sp.BL3), and Hung et al (14) described strains of Rhizobium, Bradyrhizobium and Agrobacterium that could grow in a medium containing 4.5% NaCl and also grew well at 45°C. The diversity of rhizobia nodulating Medicago species has been widely reported (3,4,10,38) including in Tunisia (1,16,(44)(45)(46). Three different species, Ensifer meliloti (17), Ensifer medicae (27) and Rhizobium mongolense (37), were reported as microbial symbionts of Medicago species.…”
mentioning
confidence: 99%
“…Neighbor-joining phylogenetic tree constructed using DNA sequences for a subset of sequenced hrrP homologs identified in the USDA Sinorhizobium collection and GenBank for the genera Rhizobium and Sinorhizobium. To help visualize the lack of concordance between the hrrP phylogeny and Sinorhizobium phylogeny, we assigned Sinorhizobium clades (I-XVI) based on the chromosomal phylogeny reported by Van Berkum et al (24).…”
Section: Methodsmentioning
confidence: 99%
“…The hrrP ORF was used to generate a neighbor-joining phylogenic tree. Clades I-XVI were assigned based on the chromosomal phylogeny reported by Van Berkum et al (24) at a linkage distance of 0.35.…”
Section: Methodsmentioning
confidence: 99%
“…61 In rhizobia the two first genes analyzed were recA and atpD 62 and currently they have been sequenced in many rhizobial species showing their usefulness in differentiation of species whose 16S rRNA genes are nearly identical. 59,60 In the last years new schemes for identification and phylogenetic analysis of bacteria named MLSA (Multilocus sequence analysis) and MLST (Multilocus sequence typing) based in the analysis of several housekeeping genes have been applied phylogenetic analyses of concrete groups of rhizobia as Ensifer [63][64][65] and Bradyrhizobium. 66,67 For instance, these studies indicate that housekeeping genes sequencing is superior to DNA-DNA hybridization for the assessment of genetic relatedness between Ensifer species and support the suggestion that Ensifer xinjiangensis is a later heterotypic synonym of Ensifer fredii.…”
Section: Recent Changes In the Taxonomy Of Rhizobiamentioning
confidence: 99%